Запорозькі козаки у Сванетії? - Мушкудіані, О. (Слово і Час, 2018)
У статті досліджено проблему переселення козаків після ліквідації Запорозької Січі
Катериною II 1775 р. Зокрема, уперше вивчено матеріали щодо поселень січовиків у Грузії, а
саме – Сванетії. До наукового дискурсу залучаються такі питання: чинники появи козаків у місцині
та її характеристика, риси аборигенів і етапи асиміляції переселенців, наслідки “міграційних”
процесів. Дослідник студіює маловідомі історико-географічні джерела, спільне та відмінне в
менталітеті, культурі, побуті сванів і січовиків. The article highlights little-known facts about the settlement of Zaporozki Cossacks in the alpine,
practically inaccessible country — Svanetia. It happened after the abolition of Zaporozka Sich
by Catherine II in 1775. The impetus for the study was a short note by H. Lebedynets “Traces of
Zaporozhians’ settlement in Svanetia”, which appeared on the pages of “Kievskaya starina” journal
in 1885. H. Lebedynets just mentioned the Cossacks’ appearance in the territory, neither planning to
name the destination country nor trying to explain what kind of land it was, what were the traditions of
local tribes etc. Addressing these and other issues, describing conditions in which the Zaporozhians
had to live in independent Svanetia became the subject of the present article. In order to perform this
task the author had to fi nd, compile and introduce to the scholarly community existing historical and
geographic sources, proving the residence and later assimilation of Cossacks in the foreign country.
It is also mentioned that after the Sich abolition Cossacks settled themselves on the banks of the
Kuban River, where they participated in constant battles with the Circassians often being captured.
Escape to the nearest and, in addition, Christian country could be the only possible salvation under
those conditions. The article also covers such issues as: geographical and historical position of Svanetia of those
times; the peculiar features of the natives, their way of life, customs, traditions etc.; similarities and
differences in the mentality of the incomers and the locals; new culture, faced by the Cossacks. The
problems of cohabitation of the like-minded Svans and Cossacks (religion, worldview, moral values,
struggle for independence, autonomy, and freedom) are being studied for the fi rst time. Describing
Svanetia of those times, the author points out the causes of assimilation of the arrived, provides
examples of entering Svan families and various Svan communities, the description of rights and duties
acquired after being admitted to the local groups. Certain attention is drawn to the features remained
from the Cossacks to nowadays, such as: man’s hairstyle — a little lock of hair on a shaved head
in some of Svan families, particularly in Mestia, as well as the existence of ‘sankvira’, the shortened
variant of Ukrainian ‘trembita’, in the independent Svanetia used to gather people with its sound in
case of military or other important social and public needs. At the end of the article the author briefly reports on the settlement of the Zaporozki Cossacks in Western Georgia on the Black Sea coast before the 17th century. Статья посвящена изучению причин и
последствий переселения запорожских
казаков с Кубани в Сванетию. В работе
анализируются исторические и географические материалы. Впервые
изучается проблема сосуществования
запорожцев и сванов как близких по духу
общин (религия, мировоззрение, моральные
ценности, борьба за независимость). Автор
исследует путь казаков из черкеского плена
в Грузию, где они нашли дружбу и новое отечество.